Comparative analysis of fruit quality parameters and volatile compounds in commercially grown citrus cultivars - Polat Yakup; Cimen Berken; Celik Ferit; Ekşi Esra; Koc Gokmen; Ercisli Sezai; Assouguem Amine; Aberkani Kamal; Iqbal Zafar; Mehta Chandra Mohan; Kafkas Nesibe Ebru (Open Chemistry)
This study compared key fruit quality parameters among seven commercially grown citrus cultivars (kumquat, limequat, Moro blood, Alacalı calamondin, Lem-onquat, pink lemon, Indio mandarinquat) from different species. Total phenolic content ranged from 92.37 to 550.28 mg gallic acid equivalent/g, and total antioxidant capacity varied from 65.03 to 92.74%. Sucrose was identified as the predominant sugar across all cultivars, with the highest content (63.66 g/kg) found in “Moro blood.” Citric acid was the major organic acid present in all varieties, with “Pink lemon” exhibiting the highest level (58.91 g/kg). l-Ascorbic acid, valued for its vitamin and antioxidant properties, reached its peak (1.03 g/kg FW) in the Moro blood variety. Volatile compound analysis was conducted using gas chromatography/mass spectrometry with solid-phase micro extraction (SPME) fibres (blue, red, and grey) for both fruit peel and juice. Dl-Limonene was identified as the predominant volatile compound in both peel and juice extracts across all SPME fibres used.